2017
DOI: 10.1111/imb.12292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the proliferation and excretion of Bartonella quintana between body and head lice following oral challenge

Abstract: Human body and head lice are highly related hematophagous ectoparasites but only the body louse has been shown to transmit Bartonella quintana, the causative agent of trench fever. The mechanisms by which body lice became a vector for B. quintana, however, are poorly understood. Following the oral challenge, green fluorescence protein-expressing B. quintana proliferated over 9 days post-challenge with the number of bacteria being significantly higher in whole body versus head lice. The numbers of B. quintana d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…For example, in body lice, the B. quintana proliferation rate in the gut was significantly higher (2.0-12.1-fold) over time when compared with head lice until 12 days post-challenge. The viability index of B. quintana in the feces over the entire 11 days post-challenge was 6.4-10.6-fold higher in body lice compared to head lice (Kim et al, 2017). The reduction of the immune response in body lice may be partly the consequence for their increased competence as a vector, compared to head lice (Kim et al, 2011(Kim et al, , 2012(Kim et al, , 2017Previte et al, 2014), which develop a more effective immune response to restrict bacterial replication.…”
Section: Head Louse Associated Pathogensmentioning
confidence: 92%
See 4 more Smart Citations
“…For example, in body lice, the B. quintana proliferation rate in the gut was significantly higher (2.0-12.1-fold) over time when compared with head lice until 12 days post-challenge. The viability index of B. quintana in the feces over the entire 11 days post-challenge was 6.4-10.6-fold higher in body lice compared to head lice (Kim et al, 2017). The reduction of the immune response in body lice may be partly the consequence for their increased competence as a vector, compared to head lice (Kim et al, 2011(Kim et al, , 2012(Kim et al, , 2017Previte et al, 2014), which develop a more effective immune response to restrict bacterial replication.…”
Section: Head Louse Associated Pathogensmentioning
confidence: 92%
“…Recently, several studies have performed comparative analyses in the immune responses following the bacterial challenge using in vitro-rearing system and have shown that body lice relative to head lice show a significant reduction in immune responses, particularly at the onset of the immune challenge (Kim et al, 2011(Kim et al, , 2012(Kim et al, , 2017Previte et al, 2014). In one study in particular, Kim et al (2017) demonstrated that, as in the case of body lice, head lice can withstand a persistent charge of B. quintana infection for several days following the acquisition in a bloodmeal and spread in their feces viable bacteria. However, the rates of proliferation in the gut and numbers of viable B. quintana in the feces were significantly lower in head lice compared to body lice (Kim et al, 2017).…”
Section: Head Louse Associated Pathogensmentioning
confidence: 99%
See 3 more Smart Citations